Chloroform and desflurane immobilization with recovery of viable Drosophila larvae for confocal imaging. - Cevik, D.; Acker, M.; Arefi, P.; Ghaemi, R.; Zhang, J.; Selvaganapathy, P.R.; Dworkin, I.; Jacobs, J.R. (Journal of Insect Physiology, 2019)
Imaging of living, intact Drosophila larvae is challenged if normal bodily function must be observed or when healthy larvae must be recovered for subsequent studies. Here, we describe a simple and short protocol that employs transient airborne chloroform or desflurane (1,2,2,2-tetrafluoroethyl difluoromethyl ether) to efficiently immobilize larvae without the use of manipulation devices, vaporizers or imaging chambers. This non-lethal method allows the use of anesthetics while allowing tracking of individual Drosophila into adulthood for follow-up experiments. At dosages sufficient to immobilize larvae, Desflurane, but not chloroform reduced the central nervous system response to auditory stimulus. Desflurane doses were sufficient to arrest the heart, however significant rapid recovery was observed. With our method, chloroform provided more rapid anesthesia but slower recovery than Desflurane. Without specialized hardware, this technique allows for repeated imaging of living Drosophila larvae.